Retrato da verbo-visualidade em livros didáticos do ensino fundamental: uma abordagem dialógica - Costa, Elizangela Patrícia Moreira da (2016)
This thesis aims at understanding how the utterances constituted in/by verbal-visuality as expression plan, present in two collections of Portuguese Language textbooks (LDP) of Elementary School, can collaborate to the formation of a critical reader, in this phase of teaching in which the reading capabilities are in full development. The corpus consisted of two collections designed to the third and fourth cycles (6th to 9th years) of Elementary School, namely: To live together: Portuguese, from SM Publisher, and Portuguese: languages, from Saraiva Publisher, published in 2012, recommended by the National Program of the Textbook – PNLD – (BRAZIL, 2013) and selected from the choice of Portuguese teachers of two public schools of Cuiabá-MT. The interest for the subject was motivated by the results arising from the Master research in Language Studies, carried out in the UFMT (Federal University of Mato Grosso) (COSTA, 2011). The objects consisted of the High School LDP to understand how the inclusion of genres which link verbal and visual materiality in its composition contributed to the reading skills education of young students from the final years of basic education. In the dissertation, it was observed the scarcity of visual and verbal-visual genres in specific reading activities and its approach proved itself little fruitful to mobilize reading capabilities to their specificities. In this investigation, proceeding with the initial studies, it was taken as object the LDP of Elementary School. It has been assumed that approaches of discursive genres which are constituted in/by the verbal-visual plan, present in the Elementary School collections, would not collaborate for the reading skills education of young students at this educational level. It is argued that considering the verbal and the visual dimension of an utterance as unique and indissoluble, in reading approaches in relation to verbal-visual discursive genres, in the teaching-learning project of selected textbooks, will contribute to a good work of reading skills education of young students who have access to these books in the Brazilian basic education. Therefore, the work is based on the dialogical language theory by Bakhtin and the Circle, in the conceptions of concrete utterances, dialogical relationships and active and creative understanding, combining them to the studies of verbal-visual dimension of the utterance developed by Brait (2009; 2012). It is a research of documental analysis of dialogical approach. In order to develop it, discursive genres constituted in/by verbal-visual plan included in the selected objects were analyzed, seeking to observe in which way its approach can contribute to educate students in response to the reading demands of the contemporary world. Thus, answers were sought to the following questions of investigation: 1. Which discursive genres constituted in/by the verbal-visual plan are present in two collections of LDP from the 6th to the 9th years of Elementary School? 2. How is the verbal-visual materiality in the selected LDP treated? 3. How does the treatment of verbal-visual materiality, in the selected activities, can contribute to the active and creative understanding of the text and for the development of reading capabilities for the specificities of a verbal-visual utterance? This study is justified due to the need of reflecting on the place of verbal-visuality in Portuguese textbooks and reading skills education of young students in Brazilian schools. The result of the analyses pointed to the scarcity of verbal-visual discourses in specific reading activities, revealing that the inclusion in activities whose aim is the reading skills education of the student brings little contribution to the recognition of the verbal-visual dimension of the utterance as indissoluble, which render impossible the development of special capabilities for the reading of verbal-visual utterances. In light of this, an activity of reading practice was formulated as contribution of this investigation to the teacher and researchers in the area of mother-tongue teaching and as a proposition of a possible way to teaching-learning of critical reading, from the observation and consideration of verbal-visual materiality of the utterance as indissoluble, thus, making it possible the development of capabilities for its understanding in an active and creative way